Answer:
x1= -7 , x2= 1
Step-by-step explanation:
<span>Simplifying
4(y + -3) = 6(y + 2)
Reorder the terms:
4(-3 + y) = 6(y + 2)
(-3 * 4 + y * 4) = 6(y + 2)
(-12 + 4y) = 6(y + 2)
Reorder the terms:
-12 + 4y = 6(2 + y)
-12 + 4y = (2 * 6 + y * 6)
-12 + 4y = (12 + 6y)
Solving
-12 + 4y = 12 + 6y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-6y' to each side of the equation.
-12 + 4y + -6y = 12 + 6y + -6y
Combine like terms: 4y + -6y = -2y
-12 + -2y = 12 + 6y + -6y
Combine like terms: 6y + -6y = 0
-12 + -2y = 12 + 0
-12 + -2y = 12
Add '12' to each side of the equation.
-12 + 12 + -2y = 12 + 12
Combine like terms: -12 + 12 = 0
0 + -2y = 12 + 12
-2y = 12 + 12
Combine like terms: 12 + 12 = 24
-2y = 24
Divide each side by '-2'.
y = -12
Simplifying
y = -12</span>
Slope = (6 - 3)/(-2-2)
= 3/-4
= -3/4
answer
slope = -3/4
Answer:
6; 22; 20 (ft.)
Step-by-step explanation:
1) if the length of the each side are: n; 4n-2 and 4n-4, then the expression of the perimeter can be written: P=n+4n-2+4n-4 or P=9n-6.
2) if according to the condition perimeter is 48 (ft.), then
9n-6=P; ⇔ 9n-6=48; n=6.
3) if n=6, then the required lengths of the sides are:
n=6 (ft.);
4n-2=22 (ft.);
4n-4=20 (ft.)
it would be C 12' 71/8" x 21' 71/8"
and sorry for what I said and did